Regional Seismic and Tsunami Susceptibility Assessment of ChennaiNagapattinam Coast of Tamilnadu and Pondicherry (International Journal of Emerging Trends in Science and Technology, 2017)
Coastal areas in general and Tamilnadu Coast in particular is experiencing rapid urbanization and put tovariety of uses. The threat of natural disaster for the shore based activities is ever increasing and thesusceptibility status of earthquake and Tsunami with respect to coastal tectonics for the ChennaiNagapattinam coast of Tamil Nadu and Pondicherry is analysed regionally in this study. The studyrevealed the requirement of on shore and offshore beach ridges mapping, dating and understanding itsemergence in combination with paleo seismicity. Further it is emphasised that the historical and paleotsunami deposits identification and using this data for the future prognosis is vital for managing the futureTsunami disasters. Based on the available geological and tectonic information it can be inferred that eventhough the offshore areas adjoining the Tamilnadu coast appears to be low to moderately susceptible forearthquake and tsunami generation, understanding the neotectonism and detailed research in the gap areasfor the studied coastal sector have been highlighted in this study.